Accession of the Russian Orthodox Church to the World Council of Churches in the context of church-state relations in the USSR - Sergey Zvonarev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The accession of the Russian Orthodox Church to the World Council of Churches in 1961 was the result of Moscow’s revision of its previous position, as well as a great deal of preparatory work led by Metropolitan Nikodim (Rotov), Chairman of the Department for External Church Relations. The Russian Church was not free to make such an important decision. The Soviet authorities regarded the membership of the churches of the USSR and the Eastern European Socialist Bloc countries in the WCC as an obstacle to the transformation of the international Christian organization into an instrument of the Western states’ struggle against socialism as a whole and the Soviet Union in particular. The expansion of the eastern flank of the Council changed the modality of the organization from pro-Western to all-Christian. This destroyed a springboard for the anti-Soviet policy of Western states, primarily the United States, Great Britain and the Federal Republic of Germany. The Russian Church, around which allied churches and some representatives of Western churches were consolidated, became a counterweight to the influential Anglo-American Bloc in the WCC. At the same time, thanks to the diplomatic talent of Metropolitan Nicodim, Soviet foreign policy priorities did not absorb the Church’s interests, and the Russian Church had the opportunity to reach the inter-Christian level and overcome isolation within the Soviet Union.